2020
DOI: 10.1002/ecs2.3153
|View full text |Cite
|
Sign up to set email alerts
|

Highly competent native snake hosts extend the range of an introduced parasite beyond its invasive Burmese python host

Abstract: Romagosa. 2020. Highly competent native snake hosts extend the range of an introduced parasite beyond its invasive Burmese python host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…To the best of our knowledge, this represents the first record of R. orientalis parasitizing any gecko, and only its second lizard host, having recently been reported from the Argentine Giant Tegu (Salvator merianae) (Goetz et al 2021). Our finding is surprising, given that adults are known to parasitize snakes (Ali et al 1982;Miller et al 2020) and that the species is not reported to parasitize G. gecko in their sympatric native range (e.g., Burma, India, Philippines; Ali et al 1982;Rösler et al 2011). The exploitation of novel hosts by R. orientalis might result from its ability to exhibit hostspecific phenotypic plasticity (Westfall et al 2019), which, when coupled with the plethora of immunologically naïve hosts within the pentastomes' North American invasive range, may ultimately enable this parasite to infect a variety of novel intermediate and definitive hosts in Florida.…”
Section: Reptiles and Amphibians C O N S E R V At I O N A N D N At U R A L H I S T O R Ymentioning
confidence: 73%
See 1 more Smart Citation
“…To the best of our knowledge, this represents the first record of R. orientalis parasitizing any gecko, and only its second lizard host, having recently been reported from the Argentine Giant Tegu (Salvator merianae) (Goetz et al 2021). Our finding is surprising, given that adults are known to parasitize snakes (Ali et al 1982;Miller et al 2020) and that the species is not reported to parasitize G. gecko in their sympatric native range (e.g., Burma, India, Philippines; Ali et al 1982;Rösler et al 2011). The exploitation of novel hosts by R. orientalis might result from its ability to exhibit hostspecific phenotypic plasticity (Westfall et al 2019), which, when coupled with the plethora of immunologically naïve hosts within the pentastomes' North American invasive range, may ultimately enable this parasite to infect a variety of novel intermediate and definitive hosts in Florida.…”
Section: Reptiles and Amphibians C O N S E R V At I O N A N D N At U R A L H I S T O R Ymentioning
confidence: 73%
“…1 insert), an obligate parasite that infects the lungs of snakes as its primary host, is native to Asia, Africa, and possibly Italy (Ali et al 1982;Christoffersen and De Assis 2013); it is co-invasive with the Burmese Python (Python bivittatus) in Florida (Miller et al 2018). Raillietiella orientalis has spilled over from pythons to infect 14 of Florida's native species of snakes (Miller et al 2018(Miller et al , 2020Metcalf et al 2019), and is expanding its range northward beyond the range of the Burmese Python via these highly competent novel snake hosts (Miller et al 2020), with R. orientalis detected in native snakes as far north as Alachua County (Walden et al 2020). Herein we report the first record of R. orientalis parasitizing G. gecko.…”
Section: Reptiles and Amphibians C O N S E R V At I O N A N D N At U R A L H I S T O R Ymentioning
confidence: 99%
“…There is considerable research focusing on direct negative impacts of Burmese pythons in southern Florida. However, indirect effects may profoundly affect native ecosystems, including the spread of pathogens (e.g., serpentovirus) and parasites to native species, alteration of host-parasite dynamics (e.g., Miller et al 2020;Burkett-Cadena et al 2021), and trophic cascades resulting from the direct suppression of mammal populations in southern Florida (Willson et al 2011).…”
Section: Indirect Ecological Impactsmentioning
confidence: 99%
“…About 13% of pythons in Florida are infected with R. orientalis (Miller et al 2020), a species of pentastome lung parasite known to infect pythons and a wide variety of other southeast Asian snakes in the python's native range (Christoffersen and De Assis 2013). This lung parasite now infects native snakes in southern Florida through parasite spillover (Miller et al 2018).…”
Section: Parasites and Pathogensmentioning
confidence: 99%
See 1 more Smart Citation